2015
DOI: 10.1111/ejn.13015
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus accumbens dopaminergic neurotransmission switches its modulatory action in chronification of inflammatory hyperalgesia

Abstract: Dopaminergic neurotransmission in the nucleus accumbens, a central component of the mesolimbic system, has been associated with acute pain modulation. As there is a transition from acute to chronic pain ('chronification'), modulatory structures may be involved in chronic pain development. Thus, this study aimed to elucidate the role of nucleus accumbens dopaminergic neurotransmission in chronification of pain. We used a rat model in which daily subcutaneous injection of prostaglandin E2 in the hindpaw for 14 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 48 publications
0
25
1
3
Order By: Relevance
“…Recent data from our group demonstrated that chronic stimulation of the mesolimbic dopaminergic system by intra‐NAc administration of a dopamine reuptake inhibitor facilitated the development of persistent hyperalgesia induced by PGE2 administered in peripheral tissue (Dias et al., ). This study also demonstrated that acute stimulation of the mesolimbic dopaminergic system induces analgesia via dopamine D2 receptor activation, while chronic stimulation of this system may induce plastic changes which lead to persistent hyperalgesia.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent data from our group demonstrated that chronic stimulation of the mesolimbic dopaminergic system by intra‐NAc administration of a dopamine reuptake inhibitor facilitated the development of persistent hyperalgesia induced by PGE2 administered in peripheral tissue (Dias et al., ). This study also demonstrated that acute stimulation of the mesolimbic dopaminergic system induces analgesia via dopamine D2 receptor activation, while chronic stimulation of this system may induce plastic changes which lead to persistent hyperalgesia.…”
Section: Discussionmentioning
confidence: 98%
“…The NAc seems to play an important role in pain modulation (Altier & Stewart, ; Gear, Aley, & Levine, ; Magnusson & Martin, ; Tambeli, Parada, Levine, & Gear, ; Tambeli, Quang, Levine, & Gear, ; Taylor, Joshi, & Uppal, ). Our group recently demonstrated that the NAc has a facilitatory role in persistent inflammatory hyperalgesia that contributes to the chronification of pain in a dependent manner of the dopaminergic neurotransmission (Dias et al., ). Moreover, there is a robust body of evidence indicating the involvement of the dopaminergic mesolimbic system in depressive‐like behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, the original model showed that 14 successive days of intraplantar injection of PGE2 was sufficient to induce persistent hyperalgesia in rodents for more than 30 days after the last PGE2 injection (Ferreira et al, 1990;Villarreal et al, 2009). Here we used a PGE2-induced PH-ST protocol with only seven successive days of intraplantar injection of PGE2, which is not enough to produce persistent hyperalgesia (Ferreira et al, 1990;Dias et al, 2015). Pharmacological studies revealed the role of noninflammatory agents during the hyperalgesia induction, such as PKA (protein kinase A), PKCε (protein kinase C isoform ε), AC (adenylyl cyclase) (Sachs et al, 2009;Villarreal et al, 2009), and NF-κB (nuclear factor kappa-B) (Souza et al, 2015).…”
Section: Prostaglandin E2-induced Persistent Hyperalgesia Short-term mentioning
confidence: 99%
“…Briefly, the original model showed that 14 successive days of 10 intraplantar injection of PGE2 was sufficient to induce persistent hyperalgesia in rodents for more 11 than thirty days after the last PGE2 injection (Ferreira et al, 1990;Villarreal et al, 2009). However, 12 here we used a PH-ST protocol with only seven successive days of intraplantar injection of PGE2, 13 which was not enough to produce persistent hyperalgesia (Dias et al, 2015;Ferreira et al, 1990). 14 This model was advantageous compare to others' CP models because further pharmacological studies 15 revealed a key role of non-inflammatory agents in the chronification process, such as PKA (protein 16 kinase A), PKCε (protein kinase C isoform ε), AC (adenylyl cyclase) (Sachs et al, 2009;Villarreal 17 et al, 2009) and NF-κB (nuclear factor kappa-B) (Souza et al, 2015).…”
Section: Prostaglandin E2-induced Persistent Hyperalgesia Short-term mentioning
confidence: 99%
“…These findings support a study by Song et al (2017) when they found an increase of pain behaviors 22 promoted by an HFD regardless of weight gain. Although the authors found an increased macrophage 23 density in the dorsal root ganglia and increased pain behaviors (Song et al, 2017), they did not 24 investigate any potential effect of an HFD and sedentary behavior in the NAc, a key structure in the 25 CP susceptibility (Dias et al, 2015;Schwartz et al, 2017;Zhang et al, 2019). 26 Furthermore, we reported here that the voluntary PA prevented CP susceptibility promoted by an 27 HFD and sedentary behavior.…”
Section: Differential Gene Expression In the Nucleus Accumbens -Transmentioning
confidence: 99%